José María Arguedas y los trabajadores obreros de la Universidad Nacional Agraria La Molina. Una mirada desde la sociabilidad - Díaz Barba, Armando Edwin (2023)
The present work deals with the interactions of José María Arguedas with the blue-collar workers of the National Agrarian University La Molina through the study of Simmelian sociability, that is, sociability as a playful form of socialization as Simmel calls it. The use of the microsociological approach has allowed us to get closer to detailing the smallest, apparently inconsequential parts of these interactions such as generosity, humor, greetings, jokes and others. On the other hand, the use of relational sociology makes it possible to understand depth of Arguedas's infinite abilities to establish human relationships. To collect the information, some former workers have been interviewed who, having worked at the university when Arguedas was a professor, have interacted with him, or have known him, or have heard of him. The hermeneutic method was used in the analysis of the interviews, which consists of finding meaning in the information collected in the interviews.